Changes

Jump to navigation Jump to search
2 bytes added ,  01:40, 29 September 2015
Line 569: Line 569:  
  c = 0;
 
  c = 0;
 
  G1 = tf([m*l^2+I b -m*g*l],
 
  G1 = tf([m*l^2+I b -m*g*l],
         [(M+m)*(m*l^2+I)-m^2*l^2 (M+m)*b+(m*l^2+I)*c -(M+m)*m*g*l+b*c -m*g*l*c 0])
+
         [(M+m)*(m*l^2+I)-m^2*l^2 (M+m)*b+(m*l^2+I)*c -(M+m)*m*g*l+b*c -m*g*l*c 0]);
 
  G2 = tf([-m*l],
 
  G2 = tf([-m*l],
         [(M+m)*(m*l^2+I)-m^2*l^2 (M+m)*b+(m*l^2+I)*c -(M+m)*m*g*l+b*c -m*g*l*c])
+
         [(M+m)*(m*l^2+I)-m^2*l^2 (M+m)*b+(m*l^2+I)*c -(M+m)*m*g*l+b*c -m*g*l*c]);
 
</syntaxhighlight>}}
 
</syntaxhighlight>}}
  
501

edits

Navigation menu